The influence of source molecule structure on the low temperature growth of nitrogen-doped graphene1. Issue 21 (7th June 2015) - Katoh, Tokio; Imamura, Gaku; Obata, Seiji; Bhanuchandra, M.; Copley, Graeme; Yorimitsu, Hideki; Saiki, Koichiro
<x xml:space="preserve">Abstract</x> Doping of heteroatoms such as nitrogen into the lattice structure of graphene can tune and tailor the overall electronic properties.